Trends in diabetes medications in Canada, England, Scotland and Australia: a repeated cross-sectional analysis (2012-2017) - Kalia, Sumeet (International Journal of Population Data Science, 2020)
Background We studied the uptake of new classes of glucose lowering medications, such as Dipeptidyl peptidase-4 inhibitors (DPP4s) and Sodium-glucose cotransporter 2 inhibitors (SGLT2s) amongst patients living with type 2 diabetes. We compared this in Australia, Canada, England and Scotland, and explored whether these new drugs are supplementing or replacing older classes of medications. Research Design and Methods We used primary care Electronic Medical Data on prescriptions (Canada, UK) and dispensing data (Australia) from 2012 to 2017. We included persons aged 40 years or over on at least one glucose lowering medication in each year of interest; we excluded those on insulin only. We determined proportions of patients in each nation on each class of medication, as well as on combinations of classes. Results In 2017, data from 28,063 patients in Canada, 106,000 in Australia, 88,953 in England and 15,603 in Scotland were included. The proportion of patients on metformin increased by 3.4% in Australia (95% CI: 3.24% to 3.55%) and decreased in the other nations. Canada had the greatest decrease, at 4.7% (95% CI: -5.05% to -4.34%). Sulfonylurea use decreased in most nations, while DPP4s increased in all. By 2017, between 10.1% and 15.3% of patients were on a SGLT2 and the use of either a DPP4 or SGLT2 combined with metformin approached or exceeded the use of sulfonylureas with metformin. Conclusions Newer, more expensive medications are replacing sulfonylureas and, to a lesser degree, metformin. The effects of these trends on health outcomes and overall costs should be examined.